👤
a fost răspuns

1)

Efectuați folosind formula (a-b)(a+b)=a²-b²:

a)

(3x-4)(3x+4)

b)

(5x-2)(5x+2)

2)

Efectuați folosind formula (a-b)(a+b)=a²-b²:

a)

(x-1/3)(x+1/3)

b)

(x-1/4)(x+1/4)

3)

Efectuați folosind formula (a-b)(a+b)=a²-b²:

a)

(√5x-3)(√5x+3)

b)

(√2x-√7)(√2x+√7)

4)

Efectuați folosind formula (a-b)(a+b)=a²-b²:

a)

(x-2)(x+2)(x²+4)

b)

(x-5)(x+5)(x²+25)

5)

Calculați folosind formula:(a-b)(a+b)=a²-b².

a)

(2-√3)(2+√3)-(√5-1)(√5+1)

b)

(2√5-1)(1+2√5)+(√13+7)(7-√13)

Trebuie cu rezolvare!!!